Salt concentration effects in planar light-emitting electrochemical cells - Reenen, Stephan van; Matyba, Piotr; Dzwilewski, Andrzej; Janssen, René A. J.; Edman, Ludvig; Kemerink, Martijn (Advanced functional materials, 2011)
Incorporation of ions in the active layer of organic semiconductor devices may lead to attractive device properties like enhanced injection and improved carrier transport. In this paper, we investigate the effect of the salt concentration on the operation of light-emitting electrochemical cells, using experiments and numerical calculations. The current density and light emission are shown to increase linearly with increasing ion concentration over a wide range of concentrations. The increasing current is accompanied by an ion redistribution, leading to a narrowing of the recombination zone. Hence, in absence of detrimental side reactions and doping-related luminescence quenching, the ion concentration should be as high as possible.